FOREWORD - Van Harte, E.L. (Scientia Militaria - South African Journal of Military Studies, 2011)
Scientia Militaria: the South African Journal of Military Studies, initially known as Militaria:Periodical for Military History, was published for the first time in 1969 by the Military Archives, but through negotiations between the faculty at the Military Academy and the Director of the Military Archives the Journal found a new home in the Faculty of Military Science in January 1997. Several committed academics served as editors, including the likes of Deon Visser, Ian van der Waag, Theo Neethling and Francois Vreÿ. They and many others before 1997 sustained the publication of this journal over the last 40 years. To all of those who have contributed to the sustainability of the journal, be it through the writing of articles, the securing of funds, or by serving on the editorial board, we express our greatest appreciation for making sure that Scientia Militaria could appear as a biannual journal.